Monitoring green biomass utilizing remote sensing techniques for agriculture and forest areas in East Malaysia - Mohd Razali, Sheriza; Samdin, Zaiton; Lion, Marryanna; Atuchar, Arnaldo Marin (Institute of Physics Publishing, 2022)
Forests and agricultural plantations are vegetated areas that play an important role in catering to human needs. The characteristics of the two lands can be recognized by utilizing remote sensing techniques of WorldView-2 satellite images as green biomass monitoring tools. The research was undertaken in Sabah Softwoods Berhad (SSB) forest plantation, East Malaysia, to analyze land use in the high functionality areas. Aside from the social benefits, there has been a lack of research conducted to estimate the areas' Net Primary Productivity (NPP) using remote sensing of biophysical characteristics. The NPP quantifies the biomass generated by the green plants, which provides the chemical energy that drives most of the biotic processes on the Earth. The NPP calculated from the study for all land features in the study areas ranged from 39.33 gCm−2 month−1 to 1498.00 gCm-2 month-1. This work has established a new NPP assessment for all land features in the Brumas forest plantation in East Malaysia. Because NPP is an estimate of the earth's living biomass, this type of approach should be used to develop biomass maps to meet human requirements on the planet.